Microglial Dynamics During Human Brain Development - Menassa, David A.; Gomez-Nicola, Diego (Frontiers in Immunology, 2018)
Microglial cells are thought to colonise the human cerebrum between the third and 22nd gestational weeks. Rodent studies have demonstrated that these cells originate from yolk sac progenitors though it is not clear whether this directly pertains to human development. Our understanding of microglial cell dynamics in the developing human brain comes mostly from post-mortem studies demonstrating that the beginning of microglial colonisation precedes the appearance of the vasculature, the blood-brain barrier, astrogliogenesis, oligodendrogenesis, neurogenesis, migration and myelination of the various brain areas. Furthermore, migrating microglial populations cluster by morphology and express differential markers within the developing brain and according to developmental age. With the advent of novel technologies such as RNA-sequencing in fresh human tissue, we are beginning to identify the molecular features of the adult microglial signature. However, this is may not extend to the much more dynamic and rapidly changing antenatal microglial population and this is further complicated by the scarcity of tissue resources. In this brief review, we first describe the various historic schools of thought that had debated the origin of microglial cells whilst examining the evidence supporting the various theories. We then proceed to examine the evidence we have accumulated on microglial dynamics in the developing human brain, present evidence from rodent studies on the functional role of microglia during development and finally identify limitations for the used approaches in human studies and highlight under investigated questions.